Economic Evaluation of Coronary Heart Disease (CHD): Expectations and Challenges in UK and Iran - AD Parsa; D Gray (Tehran University of Medical Sciences, 2005)
Introduction: Hearth disease is a major worldwide health problem with high incidence and prevalence in developed countries and rising incidence in developing countries. During last ten years, almost 20% of all acute hospital admissions are cardiac-related. More than 25,000 bypass procedures, about 40,000 angioplasty, and other coronary intervention procedures are carried out annually in the UK. CHD burdens the UK economy by £7.06 billion. Methods: Economic evaluation involves three basic steps of cost identification, cost valuation and cost measurement. The most accepted perspective is societal. Patient data are extracted from the patient file record or patients' questionnaire or interview. Both quantitative and qualitative analyses are used. Discussion: Management is important clinically and from the economics viewpoint (e.g.; individuals and society) must be considered. CHD management is becoming increasingly costly. Direct and indirect costs divert scarce resources (patient's or family and society) to medical care. Economic evaluation assesses the value of heart management in terms of their expected costs and expected benefits, if it includes an analysis of all direct and indirect cost and also all benefits forgone. Increasingly technical solutions are deployed and consideration must be given to which would better meet health sector objectives. Health care expectations: The basic principle is simple- comprehensive, high quality medical care should be available to all without financial barriers to access. However, in the face of increasing costs and ever more patients, this is under threat. In addition, sometimes, populations in greatest need are those least likely to receive it. It is expected economic evaluation aid to define choices on how best to use resources. The current distribution of resources leaves some high- priority demands unmet. The challenge of meeting the demand free public services is increasing. Demand for CHD treatment is undoubtedly rising. Rationing and allocation choice: Resource allocation strategies are designed to manage different areas of NHS effectively. There are several approaches to rationing however; there are moral considerations that ought to be recognised. Currently, rationing is according to a range of criteria that seem challenging. With scarce resources, it is important that services be provided efficiently. Efficiency within the NHS involved improving both productive efficiency and allocative efficiency. Equity in healthcare has become a priority. Willingness to pay (WTP): By evaluating WTP, patients' preferences can be taken into account though there are difficulties in comparing user (patient) values with non-user (non-patient) values. There are also moral issues regarding the use of only economics data in decision-making. Moreover, there is need and preference conflict and requires to be managed appropriately. Conclusion: CHD growth in both developed and developing countries put health systems faced on greater demand to appropriate care. Thus, the notion of economic evaluation is to help health professional to divert resources to achieve the best health outcomes for individuals. There is an urgent need to develop preventive strategies in developing countries. Prevention and treatment strategies in developed countries should be modified for developing countries. These strategies should include approaches to prevent the development of risk factors in the population as a whole by changes in public policy as well as approaches that can be applied to high-risk individuals.